Analysis the Implementation of Communicative Language Teaching and Classroom Interaction in the Effort to Increase Learners’ Speaking Skills - Daar, Gabriel Fredi; Ndorang, Theofilus Acai (Universitas Malikussaleh, 2020)
Communicative language teaching (CLT) is a set of principles about the goals of language teaching, how learners learn a language, the kinds of classroom activities that best facilitate learning, and the roles of teachers and learners in the classroom (Richard, 2006:2). Classroom interaction occurs in the process of applying CLT which requires the participation of both learners and teacher. The study aims at finding out how CLT and classroom interaction implemented collaboratively in the effort to increase learners’ speaking skill at private senior high schools in Ruteng, Flores. It’s mixed method research combining the use of descriptive quantitative and qualitative study design with phenomenological approach. For the purpose of quantitative study, it’s chosen 123 students by using cluster random sampling, meanwhile for the purpose of qualitative data, it’s chosen 12 students and three English teachers by using purposive sampling. The research result showed that CLT characteristics (82=66.7%) and teacher’s role (98=79.7%) were mostly categorized as high level of CLT implementation. Meanwhile, material, media and learners’ role were mostly categorized as medium level. English teachers always involve their students in the productive activities. However, they mostly used book or hand out as the media to deliver materials. Integrating technology into classroom, using games as one of method to cheer up the students boredom hardly ever undertaken. Regarding the implementation of classroom interaction; initiation was mostly in the category of low level (76=61.8%). Students mostly do the activities of learning English designed by teacher. They are not engaged with learning autonomy that leads them to have self learning habit. Consequently, students are only able to accomplish the simple tasks